Urinary high-mobility group box-1 associates specifically with lupus nephritis class V. (December 2016) - Jog, N R; Blanco, I; Lee, I; Putterman, C; Caricchio, R
Introduction: High-mobility group box 1 protein (HMGB-1) has been implicated in the pathogenesis of lupus nephritis (LN). There is increased HMGB-1 expression in the kidneys and increased levels are observed in serum and urine of patients with LN. This study was performed to determine whether the increased urinary HMGB-1 was specific for active lupus or secondary to renal damage. Methods: Urine from 61 lupus patients (32 had active LN and 29 had systemic lupus erythematosus (SLE) with no evidence of LN) and 14 control proteinuric patients (all with hypertension and eight also with diabetes) were included in this study. HMGB-1 was detected by Western blot. Urine protein was normalized to urine creatinine to account for volume of the specimen. Results: Median normalized urine HMGB-1 levels were significantly elevated in LN patients compared to lupus patients without kidney disease (53.81 vs 9.46, p  < 0.001). A difference in median levels was seen between LN classes, with a significant difference between proliferative and membranous disease (33.4 vs 138.8, p  = 0.003). Urine protein to urine creatinine ratio (P/C) correlated with urinary HMGB-1 ( r  = 0.52, p  < 0.001), but across the classes this was true only for membranous disease ( r  = 0.71, p  = 0.022, proliferative, p  = 0.63; mixed, p  = 0.34). Conclusions: HMGB-1 is elevated in the urine of patients with active LN. Levels are associated with LN class, and higher levels of urinary HMGB-1 are seen in patients with class V when compared to both proliferative and mixed classes. Therefore, urinary HMGB-1 may be suggestive of membranous LN and warrants further evaluation in a large lupus cohort.